Observation of abnormal suppression of f0(980) production in p-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physics letters, 2024)
The dependence of f0(980) production on the final-state charged-particle multiplicity in p-Pb collisions at √sNN = 5.02 TeV is reported. The production of f0(980) is measured with the ALICE detector via the f0(980)→π+π− decay channel in a midrapidity region of −0.5<y<0. Particle yield ratios of f0(980) to π and K⁎(892)0 are found to be decreasing with increasing charged-particle multiplicity. The magnitude of the suppression of the f0(980)/π and f0(980)/K⁎(892)0 yield ratios is found to be dependent on the transverse momentum pT, suggesting different mechanisms responsible for the measured effects. Furthermore, the nuclear modification factor QpPb of f0(980) is measured in various multiplicity ranges. The QpPb shows a strong suppression of the f0(980) production in the pT region up to about 4 GeV/c. The results on the particle yield ratios and QpPb for f0(980) may help to understand the late hadronic phase in p-Pb collisions and the nature of the internal structure of f0(980) particle.
Gesehen am 19.05.2025
ALICE Collaboration: S. Acharya, V. Angelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yüncü, F. Zanone [und 1037 weitere]
Online verfügbar: 23. April 2024
Im Titel sind "0" und NN tiefgestellt